Natural Fiber-Reinforced Polycaprolactone Green and Hybrid Biocomposites for Various Advanced Applications - Ilyas R.A.; Zuhri M.Y.M.; Norrrahim M.N.F.; Misenan M.S.M.; Jenol M.A.; Samsudin S.A.; Nurazzi N.M.; Asyraf M.R.M.; Supian A.B.M.; Bangar S.P.; Nadlene R.; Sharma S.; et al. (MDPI, 2023)
Biocompatibility; Biomechanics; Reinforcement; Tissue; Tissue engineering; 'current; Advanced applications; Biocomposite; Environmental pollutions; Greengreen biocomposite; Hybridhybrid biocomposite; Natural fiber reinforced; Thermalthermal propertiesproperty; Tissues engineerings; Composite materials